Meeting Scheduling Assistance with Structured Workflows - Cranshaw, Justin; Elwany, Emad; Newman, Todd; Kocielnik, Rafal; Yu, Bowen; Soni, Sandeep; Teevan, Jaime; Monroy-Hernandez, Andres (Proceedings of the ACM Conference on Human Factors in Computing Systems (CHI 2017), Denver, CO, 2017)
Publication to be available after conference commencement.